Sustainability Factor Related with the Implementation of Community Mental Health Nursing (CMHN) in South and West Jakarta - Esti Winahayu; Budi Anna Keliat; Ice Yulia Wardani (Universitas Airlangga, 2014)
The aim of this study was to determine the sustainability factor related with the implementation of CMHN in South and West Jakarta. The method of the study was cross sectional, data of the nurses was collected by questionnaire of CMHN and pearson correlation was used to analyzed the data. Interviews conducted on stakeholder to get stakeholder perceptions about the sustainability factor of CMHN. The ability of nurse in the implementation of CMHN is 45,86%. The nurse perception toward sustainability factor of CMHN is 67,49%. The result of study shows the significant relationship between the sustainability factor with the implementation of CMHN. The result of analysis interviews with stakeholder about 8 sustainability factors is obtained into several themes: the positive opinion of stakeholder toward the CMHN (the existence of nursing care to the patients, detecting of new case, and reducing stigma) and the effort for the sustainability of CMHN (increasing the perception, budget planning, and socialization). The result of the study is recomended to improve the community mental health nursing service in other region.